African Canadian Anti-Discrimination Activism and the Transnational Civil Rights Movement, 1945–1965 - Waters, Rosanne (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2013)
Several recent historical works have challenged interpretations of the civil rights movement in the United States as a strictly domestic story by considering its connections to anti-racist struggles around the world. Adding a Canadian dimension to this approach, this article considers linkages between African Canadian anti-discrimination activism in the 1950s and early 1960s and African American civil rights organizing. It argues that Canadian anti-discrimination activists were interested in and influenced by the American movement. They followed American civil rights campaigns, adapted relevant ideas, and leveraged the prominent American example when pressing for change in their own country. African Canadian activists and organizations also impacted the American movement through financial and moral support. This article contributes to the study of African Canadian history, Canadian human rights history, and the American civil rights movement by emphasizing the local origins of anti-discrimination activism in Canada, while also arguing that such efforts are best understood when contextualized within a broader period of intensive global anti-racist activism that transcended national borders.